The financial lives of female sex workers in Addis Ababa, Ethiopia: Implications for economic strengthening interventions for HIV prevention. Issue 3 (4th March 2022) - Namey, Emily; Lorenzetti, Lara; O'Regan, Amy; Tenaw, Eskindir; Feleke, Engdasew; Girima, Eyerusalem
ABSTRACT: Understanding the financial context of the lives of female sex workers (FSWs) is essential to address structural drivers of HIV risk. We used a financial diary methodology to record daily financial transactions over six weeks from a stratified purposive sample ( n  = 34) of FSWs in Addis Ababa, Ethiopia. FSWs also provided information on their experience with gender-based violence and condom use. FSWs generated 90.1% of total cash from sex work, with a median weekly income of USD 60.53. They engaged mostly in protected vaginal sex, earning approximately USD 4.57 per act. Food, housing, and clothing represented the largest areas of expenditure. Around 17% of expenses were recorded as costs of sex work (e.g., alcohol). Median weekly expenditures accounted for 62% of median weekly income. Nearly all participants reported depositing money into savings at least once over six weeks, while 71% reported a loan transaction during the six-week period, most as borrowers. Findings suggest that financial literacy and formalized savings activities, with life skills and empowerment training, have potential to build FSW's economic resilience, mitigating a structural driver of sex work and HIV risk.